Exploring the relationship of cognitive function with and without COVID-19 recovered schizophrenic patients - Mehmood, Anam; Almajwal, Ali Madi; Addas, Abdullah; Zeb, Falak; Alam, Iftikhar; Sehar, Bismillah (Frontiers in Public Health, 2024)
Background The Coronavirus disease 2019 (COVID-19) is linked to the deterioration of cognitive function among individuals suffering from schizophrenia. The purpose of this study was to compare the cognitive performance of schizophrenic patients before and after COVID-19. Methods A longitudinal cohort study involving a sample of 219 individuals diagnosed with schizophrenia was enrolled between June 2022 and May 2023. The participants were split into two groups infected with COVID-19 (n = 165) and not infected with COVID-19 (n = 54). The data were gathered via a questionnaire on demographic characteristics, the Brief Assessment of Cognition in Schizophrenia (BACS), the Positive and Negative Syndrome Scale (PANSS), the Calgary Depression Scale for Schizophrenia (CDSS), the Activities of Daily Living (ADL) scale, and the Insomnia Severity Index (ISI). Results The repeated-measures ANOVA showed that Among patients diagnosed with COVID-19, there was a deterioration in global cognitive function (before COVID-19 = −2.45 vs. after COVID-19 = −3.02, p = 0.007), working memory (before COVID-19 = −2.76 vs. after COVID-19 = −3.34, p < 0.00 1), motor speed (before COVID-19 = −1.64 vs. after COVID-19 = −2.12, p < 0.001), attention and speed of information processing (before COVID-19 = −1.93 vs. after COVID-19 = −1.16, p = 0.008). multi-variable analysis showed that several factors as having a secondary grade of education (β = 0.434), experiencing insomnia (β = 0.411)and the interaction between COVID-19 diagnosis and cognition at baseline (β = 0.796) were significantly associated with cognitive deficits. At the same time, no significant associations were found between global cognition and clinical symptoms, autonomy, or depression (p > 0.05). Conclusion The COVID-19 pandemic has significantly impacted various cognitive functions, such as verbal memory, working memory, and global cognition. Insomnia has been identified as the predominant determinant of cognitive impairment, alongside the confirmation of a COVID-19 diagnosis. Additional research is imperative to elucidate the diversification of cognitive functionality observed in individuals diagnosed with schizophrenia who have acquired COVID-19.